Jaarverslag Groninger Museum 1983-1984. - Boersma, J. W.; Boiten, E. A. J.; Cornips, M. H. N. G.; Haks, Frans; Ter Hofstede, P. M.; Jorg, C. J. A.; Kolsteren, S. T. C.; Groninger Museum, Groningen (Groningen : Groninger Museum, 1987)
Inhoud: Aanwinsten Afdeling Beeldende Kunst 1983 +1984 ; Verslag van het Prentenkabinet 1983-1984 ; ...
Alkema, Wobbie ; Bertocci, Carlo ; Blade ; van den Broeck, Frank ; Clemente, Francesco ; Cragg, Tony (Anthony) ; Disler, Martin ; Florissen, Gerard ; De Haas, Alexander ; Jordens, J. ; Kantelberg, Peter ; Kleima, Ekke A. ; Klompien, M. ; Melgers, Hendrik Johan ; Quinones, Lee ; Scharf, Kenny ; Staats, J. Derksen ; Visser, Carel ; Wiegers, Jan
Nederlands
boek